Fusing formal and informal trading: Emerging practices in the livestock value chains between Kenya and Somalia - Philemon O. Ng'askie (Danish Institute for International Studies (DIIS), 2019)
Despite ambivalence towards current state reforms, Somali merchants interact with state agents in the trade corridor that connects southern Somalia to central Kenya. Since the Somalia state collapse of 1991, informal livestock value chains have expanded into north-eastern Kenya. Here, the interaction between trade operators and authorities has produced new layers of social norms, some of which govern the economic life of this area that has endured decades of structural instability through insurgencies, state repression, corruption (musuqmaasuq) and marginalization. Based on seven months of data collection on livestock trading in and around the Garissa livestock market, this working paper shows that Somali trade operators negotiate rule breaking to facilitate commodity flows between informal and formal markets. The paper identifies three different value chains - the transnational, the local, and the export - and highlights the practical norms that emerge from the transnational value chain and how they differ from those of the local chain. It further shows how Somali livestock is gradually gaining formal status as the animals cross the Somalia border into Kenya and become subject to recording, disease surveillance and selective taxation. The paper argues that the relative weakness of the state institutions in the area may work to its advantage, as it becomes a destination for investors seeking to escape dire conditions in Somalia. This paper contributes to studies of everyday state formation by providing empirical evidence from the governance of livestock value chains between Somalia and Kenya in order to suggest that working practices can support policy development for state-building processes in Somali East Africa.
Keywords: 330; Trade; Informal economy; Livestock; Corridors; Somalia; Kenya; Hybridity